Acute kidney injury induced lithium toxicity with concomitant neuroleptic malignant syndrome - Lai, Yin Ye; Mohamed Mokhtar, Normaizuwana; Samsudin, Intan Nureslyna; Thambiah, Subashini C. (China Medical University, 2024)
Lithium, despite being an indispensable agent in the treatment of psychiatric disorders, has a narrow therapeutic index and needs to be carefully administered. Neuroleptic malignant syndrome (NMS) is a rare but potentially fatal complication due to central dopaminergic blockade. This case report illustrates the challenges in lithium therapy particularly related to the development of NMS when further risk factors such as polypharmacy and dehydration are present. We report a case of a 50-year-old man with underlying bipolar affective disorder who was previously able to tolerate olanzapine and lithium well, however developed chronic lithium toxicity due to diminished lithium elimination in acute kidney injury following a two-week history of viral acute gastroenteritis. He also developed NMS which could either be triggered independently by olanzapine; lithium toxicity; or attributed by a synergistic combination from lithium and olanzapine which led to an enhanced neurotoxicity in an already unstable dopaminergic pathway. Fluid therapy and supportive care allowed the patient to recover, and he was discharged well with a lower potency neuroleptic with slow dose titration.